1994
DOI: 10.3168/jds.s0022-0302(94)76993-9
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Function In Vitro: Diapedesis and Phagocytosis

Abstract: The function of neutrophils within the mammary gland was modeled in vitro to include diapedesis and phagocytosis. The bovine mammary cell line, MAC-T3, provided a mammary epithelial monolayer for use as a biologically meaningful barrier to neutrophil diapedesis. Features included characteristic transepithelial resistance, tight junctional complexes, and polarity. Continuous readings of transepithelial resistance indicated a stable resistance over several hours. Staphylococcus aureus, at concentrations of 1 x 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Non-transfected mammary epithelial cells typically survive only 10-25 passages, whereas MAC-T cells (with the LT) have maintained growth and morphological properties after 350 passages (Huynh et al, 1991). Although oncogene "immortalization" may alter many cellular functions, MAC-T cells retain many properties of in vivo mammary epithelial cells, such as the presence of tight junctions, gap junctions, as well as the ability to differentiate (synthesis of caseins, lactose, and lipids) in response to prolactin and appropriate extracellular matrices (Huynh et al, 1991;MacDonald et al, 1994). Likewise, LT transfected mammary fibroblasts are growth ar-rested when cultured in the absence of appropriate hormonelgrowth factor stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Non-transfected mammary epithelial cells typically survive only 10-25 passages, whereas MAC-T cells (with the LT) have maintained growth and morphological properties after 350 passages (Huynh et al, 1991). Although oncogene "immortalization" may alter many cellular functions, MAC-T cells retain many properties of in vivo mammary epithelial cells, such as the presence of tight junctions, gap junctions, as well as the ability to differentiate (synthesis of caseins, lactose, and lipids) in response to prolactin and appropriate extracellular matrices (Huynh et al, 1991;MacDonald et al, 1994). Likewise, LT transfected mammary fibroblasts are growth ar-rested when cultured in the absence of appropriate hormonelgrowth factor stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Immunity traits studied were mainly antibody response and functionality of neutrophils, which recruitment and activity are essential in the innate defence against udder infection [78,87]. Several authors [36,43,49] reported a significant sire effect of in vitro phagocytosis of blood neutrophils. Detilleux et al [19] found moderate heritabilities for migration (0.2 to 0.5) and phagocytosis (0.3-0.7) of neutrophils and for serum complement activity (0.4-0.5), using in vitro assays for 137 cows sampled three times around calving.…”
Section: Genetic Variability Of Immune Mechanisms Underlying Mastitismentioning
confidence: 99%
“…Neutrophils travel from blood to the mammary gland in response to a variety of inflammatory mediators, such as cytokines, complement and prostaglandins (Janeway et al., 2001). The phagocyting ability of the in vitro analysis of neutrophil function provides a very effective tool for the study of natural mastitis resistance (MacDonald et al., 1994).…”
Section: Introductionmentioning
confidence: 99%